2017
DOI: 10.5539/ijms.v9n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Social Cues-Customer Behavior Relationship: The Mediating Role of Emotions and Cognition

Abstract: This paper investigates the effect of social cues in a mall's shopping environment on customer behavior. Two competing mediation scenarios are assessed: emotion-cognition and cognition-emotion in a stimulus-organism-response (SOR)-based framework. Although the role of social cues in driving customer behavior in shopping contexts is largely addressed in the extant literature, the mechanism of the effect is still under-researched area and this study is an attempt to fill this gap.The conceptual model is validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
(96 reference statements)
1
8
0
Order By: Relevance
“…As stated above, suitable behavior needs further validation in future studies. By extending social atmospherics in a new context, esports attendance, our findings contributed to the line of research regarding social atmospherics in sports venues (Uhrich and Benkenstein, 2012;Chen et al, 2013;Kim et al, 2019) and retail settings regarding servicescape (Brocato et al, 2012;Nusairat et al, 2017;Avan et al, 2019). Second, grounded in the SOR framework (Mehrabian and Russell, 1974), the current study proposed a conceptual model that includes social atmospherics components to predict esports spectators' behavioral intention through their affective responses.…”
Section: Theoretical Contributionsmentioning
confidence: 67%
See 1 more Smart Citation
“…As stated above, suitable behavior needs further validation in future studies. By extending social atmospherics in a new context, esports attendance, our findings contributed to the line of research regarding social atmospherics in sports venues (Uhrich and Benkenstein, 2012;Chen et al, 2013;Kim et al, 2019) and retail settings regarding servicescape (Brocato et al, 2012;Nusairat et al, 2017;Avan et al, 2019). Second, grounded in the SOR framework (Mehrabian and Russell, 1974), the current study proposed a conceptual model that includes social atmospherics components to predict esports spectators' behavioral intention through their affective responses.…”
Section: Theoretical Contributionsmentioning
confidence: 67%
“…Walsh et al (2011) revealed the mediating effects of pleasure and arousal in the relationship between consumers' cognitions regarding the store environment and customers' behaviors. Nusairat et al (2017) indicated the mediating role of emotion and cognition in the relationship between social cues and customer behavior in a shopping mall environment. Avan et al (2019) found that positive and negative emotions served as mediators between servicescape components and behavioral responses.…”
Section: Mediating Role Of Affective Responsesmentioning
confidence: 99%
“…Walsh, Shiu, Hassan, Michaelidou, and Beatty (2011) confirmed that two emotions of pleasure and arousal differently mediate the relationship between store-related cognitions and behaviours. Nusairat, Akhorshaideh, Rashid, Sahadev, and Rembielak (2017) indicate that pleasure and cognition mediate the effect of social cues on behavioural responses.…”
Section: Mediating Role Of Emotional Statesmentioning
confidence: 99%
“…In this extent, the stimulus-organism-response (SOR) model of Mehrabian and Russell (1974) has inspired much of the previous empirical studies. The SOR model has been largely used to capture the interrelationship among the physical environment (S) customer affective and cognitive states (O) and behavioural responses (R) in different business contexts (Donovan, et al, 1994;Chang et al, 2011;Kumar & Kim., 2014;Nusairat et al, 2017;Ortegón & Royo, 2019). Nevertheless, in some cases, the model shows a deficiency on linking store environment to customer behavioural responses (e.g.…”
Section: Introductionmentioning
confidence: 99%